Are plant formins integral membrane proteins? - Cvrcková, Fatima (BioMed Central, 2000)
BACKGROUND: The formin family of proteins has been implicated in signaling pathways of cellular morphogenesis in both animals and fungi; in the latter case, at least, they participate in communication between the actin cytoskeleton and the cell surface. Nevertheless, they appear to be cytoplasmic or nuclear proteins, and it is not clear whether they communicate with the plasma membrane, and if so, how. Because nothing is known about formin function in plants, I performed a systematic search for putative Arabidopsis thaliana formin homologs. RESULTS: I found eight putative formin-coding genes in the publicly available part of the Arabidopsis genome sequence and analyzed their predicted protein sequences. Surprisingly, some of them lack parts of the conserved formin-homology 2 (FH2) domain and the majority of them seem to have signal sequences and putative transmembrane segments that are not found in yeast or animals formins. CONCLUSIONS: Plant formins define a distinct subfamily. The presence in most Arabidopsis formins of sequence motifs typical or transmembrane proteins suggests a mechanism of membrane attachment that may be specific to plant formins, and indicates an unexpected evolutionary flexibility of the conserved formin domain.